Implementation of national guidelines for the prevention and treatment of overweight and obesity in children and adolescents: a phenomenographic analysis of public health nurses’ perceptions - Nordstrand, Aina (Int J Qual Stud Health Well-being, 2016)
OBJECTIVE: To explore and describe how public health nurses (PHNs) perceive the implementation of national guidelines for the prevention and treatment of overweight and obesity among children and adolescents in well-baby clinics and school health services. DESIGN, SAMPLE, AND MEASUREMENTS: An explorative descriptive design was carried out through individual interviews with 18 PHNs and analysed according to the phenomenographic tradition. RESULTS: Four implementation strategies were described and assigned a metaphor: the structured PHN, pragmatic PHN, critical PHN, and the resigned PHN. Competence, patient receptiveness, internal consensus, interdisciplinary collaboration, resources, and organizational embedding were the determinants identified that most frequently affect implementation, and these determinants were distributed at different levels of the organization. The extent of facilitation seemed to determine which implementation strategy would be used. CONCLUSIONS: How PHNs implemented the guidelines for overweight and obesity were affected by determinants at different organizational levels. Contextual facilitation of implementation seemed better in larger organizations, but factors such as leadership, drive, and experience compensated in smaller municipalities. The implementation of guidelines was hindered when the barriers exceeded the benefits.